For the Benefit of Generations to Come or for the Sake of Survival? Measures for Protecting Forests in Early Modern Hungary - Vadas, Andras (Historical Studies on Central Europe, 2022)
The paper discusses the changes in the forest legislation on different levels of early modern administration in Hungary. By using a wide variety of sources—laws, decrees, instructive documents, and letters—it explains how forests were regarded and handled in the period of the Ottomans’ presence in the Carpathian Basin. In analyzing the sources, the paper shows how the importance of protecting and taking care of forests at different levels of administration can be attested, what the goal of this care for wooded areas was, and how the presence of the Ottoman-age wars changed the ways forests were used in the frontier and the hinterland.